Чисельне моделювання вихорових течій в напівциліндричному заглибленні за допомогою відкритих пакетів Salome, Openfoam, Paraview - Воропаєв, Геннадій Олександрович; Димитрієва, Наталія Федорівна (НТУ "ХПІ", 2019)
Чисельними методами з використанням високопродуктивних обчислювальних технологій досліджено нестаціонарну тривимірну структуру течії в напівциліндричному заглиблені. Обговорюються закономірності формування і розподілу системи вихорів, що виникають в заглиблені залежно від числа Рейнольдса, розмірів і повороту до потоку. Показано, що велику роль грають бічні стінки, що формують складну систему, що руйнує головний трансверсальний вихор та сприяє його викидам.

Transient 3D flow structure in a semi-cylindrical dimple is investigated by numerical methods using high-performance computing technologies. Patterns of formation and distribution of the system of vortices that occur in the dimples depending on the Reynolds number, size and rotation to the flow are discussed. It is shown that the side walls forming a complex system of vortices play an important role. The wall destroys the main transversal vortex and contributes to its emissions into the external flow. The proposed method of numerical simulation has shown its effectiveness in a wide range of parameters of the problem and is consistent with experimental data.
Numerical simulation of vortex flows in a semi-cylindrical dimple using Salome, Openfoam, Paraview open source packages
Keywords: генератор вихорів; керування примежовим шаром; число Рейнольдса; трансверсальний вихор; vortex generator; flow control